Pemahaman Pelecehan Seksual Para “Follower” Akun Instagram @ffa_com - Lukman Hakim; Khairunnisa Rosdiani; Jessica Lea Alexander; Dini Safitri (MediaTor (Jurnal Komunikasi), 2019)
The @ffa_com Instagram account utilizes social media to provide an understanding of harassment and campaign for anti-harassment movements to its followers. This movement being done since there is still  lack of understanding of abuse cases . The purpose of this study was to find out how much the success of the @ffa_com instagram account in campaigning anti-sexual harassment movement and to know the level of understanding of followers of the @ffa_com Instagram account towards sexual harassment itself. The study used a variable understanding of sexual harassment, with one dimension, namely understanding information, with six indicators and 25 statements. The approach of this study is quantitative with descriptive study. The population is 74 with a sample of 37 people, who are followers of the @ffa_com Instagram account. The results showed that the @ffa_com account had succeeded in providing understanding and successfully campaigning for  anti-sexual harassment to the followers of instagram account. This can be seen from the most mode found in the agreed sentence on each indicator in each statement.